The Effect of Perceived Ease of Use and Perceived Security on Customer Satisfaction on The Dana E-Wallet Transfer Feature - Marbun, Frida Wati Boru; Foster, Bob; Pramayuda, Agung (CV ODIS, 2025)
This research was conducted with the aim of finding out the description of Perceived Ease of Use and Perceived Security on Customer Satisfaction on the DANA E-Wallet Transfer Feature as well as the influence of Perceived Ease of Use and Perceived Security on Customer Satisfaction on the DANA E-Wallet Transfer Feature in Indonesia, and the lack of it. ease of use of the DANA application which is influenced by factors such as low security perceptions and low levels of trust that using the system can increase efficiency in work. The research methods used in this research are descriptive and verification methods using a quantitative approach. The population in this study is all DANA users as seen from the number of DANA application downloads on Playstore. The number of samples taken in this research was 100 respondents. The results of distributing the questionnaire were analyzed using multiple regression analysis, coefficient of determination, t test and F test. Based on the distribution of data, it was found that Perceived Ease of Use, Perceived Security and Customer Satisfaction were in the good category. Based on the results of the determination test that has been carried out on the variable, Perceived Ease of Use has an influence of 4.6% on Customer Satisfaction, Perceived Security has an influence of 60.8% on Customer Satisfaction, Perceived Ease of Use and Perceived Security have an influence of 67.9% on Customer Satisfaction. The research results show that the Perceived Ease of Use and Perceived Security variables influence Customer Satisfaction on the DANA E-Wallet Transfer Feature both partialy and simultaneously.